Digitalisation: An engine for structural change - A challenge for economic policy - Michael Hüther (Institut der deutschen Wirtschaft (IW), 2016)
Digitalisation is in everyone's hands. During the last nine years the smartphone tremendously changed private lifestyle. Anytime and everywhere we are connected, we have options for decision making and controlling in real-time. Producer of hardware as well as software service provider of platforms are driving these current structural change's aspects. However - although less visible publicly - digital transformation also includes traditional industry, this is what the buzzword "Industrie 4.0" stands for. The political and public debate on necessary control of this transformation is as much hallmarked by the search for starting points as by heated demands for targeted competition law based interventions. In this context, it has to be noted that the digital transformation's different aspects are neither adequately differentiated nor systematically captured. That is the task this contribution tackles. A classification for digital business models is developed, in order to analytically exploit the different scopes and consistently infer politico-economic need for action. – – Die Digitalisierung ist in aller Hände. Das Smartphone hat in den vergangenen neun Jahren die private Lebensführung gewaltig verändert. Jederzeit und überall sind wir vernetzt, wir haben in Echtzeit Entscheidungsoptionen und Steuerungsmöglichkeiten. Die dahinter stehenden Hersteller der Hardware und die als Dienstleister über Plattformen agierenden Softwareproduzenten sind die Treiber dieser Ausprägung des Strukturwandels. Doch - wenngleich weniger öffentlich präsent und greifbar - die digitale Transformation erfasst nicht minder intensiv die traditionellen industriellen Bereiche, das Stichwort "Industrie 4.0" steht dafür. Die politische und öffentliche Diskussion über die notwendige Steuerung dieser Transformation ist durch ein Suchen nach Ansatzpunkten ebenso geprägt wie durch lautstarke Forderungen nach gezielte Interventionen auf Basis des Wettbewerbsrechts. Dabei fällt auf, dass die verschiedenen Ausprägungen der digitalen Transformation weder hinreichend differenziert noch systematisch erfasst werden. Dieser Aufgabe stellt sich der Beitrag. Es wird eine Systematik für die digitalen Geschäftsmodelle entwickelt, um diese in verschiedenen Wirkungsbereichen analytisch zu nutzen und einen wirtschaftspolitischen Handlungsbedarf konsistent abzuleiten.
Keywords: L16; O33; L52; 330